(untitled) (Research, Society and Development, 2022)
Artisanal Minas cheese, which is made with raw milk and predominantly manual techniques, has a historical and cultural tradition related to the region where it is produced. Currently, the state of Minas Gerais in Brazil has ten regions formally recognized as producers of artisanal Minas cheese: Araxá, Campos das Vertentes, Cerrado, Serra da Canastra, Serra do Salitre, Serro, Triângulo Mineiro, Serras da Ibitipoca, Diamantina, and Entre Serras de Piedade ao Caraça. The cheese from each region has different sensory characteristics due to edaphoclimatic conditions, local microbiota, and manufacturing method, which is passed on from generation to generation. Artisanal Minas cheese has recognition as a product of high gastronomic value throughout the country. Given its economic and cultural importance, the objective of this work is to present a literature review covering the main characteristics of the producing regions and the aspects of each cheese produced in them.